2008
DOI: 10.1111/j.1365-2559.2007.02950.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A expression correlates with tumour cell type and prognosis in signet ring cell carcinoma of the stomach

Abstract: CgA expression is restricted to certain tumour cell types and may help to predict prognosis in gastric SRCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Eren et al [31] showed that 45% of gastric carcinomas had chromogranin A expression, regardless of whether they were of intestinal or signet ring type, but other authors have suggested that NE differentiation is more common in the diffuse type [30]. A recent study limited to gastric signet ring cell carcinomas demonstrated focal or diffuse chromogranin A positivity in 38 (37.3%) of 102 cases, including 15 (14.7%) with chromogranin staining in 26% to 50% of neoplastic cells and 6 (5.9%) with staining in more than 50% of neoplastic cells [32]. Notably, in this study and previously cited studies, the cases with NE immunopositivity appear to represent tumors with amphicrine differentiation because the NE positivity occurred in classical and nonclassical signet ring cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Eren et al [31] showed that 45% of gastric carcinomas had chromogranin A expression, regardless of whether they were of intestinal or signet ring type, but other authors have suggested that NE differentiation is more common in the diffuse type [30]. A recent study limited to gastric signet ring cell carcinomas demonstrated focal or diffuse chromogranin A positivity in 38 (37.3%) of 102 cases, including 15 (14.7%) with chromogranin staining in 26% to 50% of neoplastic cells and 6 (5.9%) with staining in more than 50% of neoplastic cells [32]. Notably, in this study and previously cited studies, the cases with NE immunopositivity appear to represent tumors with amphicrine differentiation because the NE positivity occurred in classical and nonclassical signet ring cells.…”
Section: Discussionmentioning
confidence: 94%
“…Two other patients with composite signet ring/glandular/NECs reported by Fujiyoshi et al [19] also survived for at least 12 years and 18 years. In a recent study that focused exclusively on signet ring cell carcinomas, chromogranin A immunopositivity was found to be an independent predictor of longer overall survival, and there was a trend toward improved survival with increasing degrees of chromogranin positivity [32]. Using immunohistochemistry for proliferating cell nuclear antigen and bromodeoxyuridine labeling, Ooi et al [29] and others [28] have shown that almost all NE cells in gastric adenocarcinomas are in a quiescent, nonproliferative state because of cell cycle arrest in G 0 or early G 1 phase.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in concert with the description of diverse cell types noticed within the realm of gastric SRCC [31,35], the present lesions featured in addition to a component of classical SRC, constituting less than 50% of the examined tumor cell population, a predominance of lesional cells, sized and shaped as SRC but void of its classical cytomorphology. This predominant, "aberrant" cell, best corresponding to the anaplastic subtype of the gastric counterpart [36], occasionally featured minute cytoplasmic mucin droplets that failed to significantly displace the nucleus or otherwise modify its morphology and thereby readily passed unnoticed on HEstained sections.…”
Section: Discussionmentioning
confidence: 92%
“…Though not meeting the strict quantitative criteria for SRCC, frequently quoted [29] histological features of the present lesions are shared with variants of SRCC [26,[30][31][32][33][34]. Thus, in concert with the description of diverse cell types noticed within the realm of gastric SRCC [31,35], the present lesions featured in addition to a component of classical SRC, constituting less than 50% of the examined tumor cell population, a predominance of lesional cells, sized and shaped as SRC but void of its classical cytomorphology.…”
Section: Discussionmentioning
confidence: 99%
“…The light microscopic appearance of uniformly small-to medium-sized tumor cells with scanty cytoplasm growing in solid sheets is important, and chromogranin and NSE are immunohistochemically useful markers [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%